ANALISA POLA PEKERJAAN LULUSAN STMIK BUDI DARMA MENERAPKAN METODE C4.5 - Anisa, Anisa; Mesran, Mesran (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Data mining is mining or discovery information to the process of looking for patterns or information that contains the search trends in a number of very large data in taking decisions on the future.In determining the patterns of classification techniques garnered record (Training set). The class attribute, which is a decision tree with method C 4.5 builds upon an algorithm of induction can be minimised.By utilizing data jobs graduates expected to generate information about interest & talent, work with benefit from graduate quisioner alumni. A pattern of work that sought from large-scale data and analyzed by various algorithms to compute the C 4.5 can do that work based on the pattern of investigation patterns that affect so that it found the rules are interconnected that can result from the results of the classification of objects of different classes or categories of attributes that influence to shape the patterns of work. The application used is software that used Tanagra data mining for academic and research purposes.That contains data mining method explored starting from the data analysis, and classification data mining.Keywords: analysis, Data Mining, method C 4.5, Tanagra, patterns of work